FAKTOR-FAKTOR PENYEBAB RENDAHNYA HASIL BELAJAR SISWA: Studi pada materi Qur’an Hadist di MA Ar-Rahma Desa Air Meles Atas - Febrika Herwani (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2020)
Learning outcomes certainly depend on the learning process. The process significantly influenced by several factors. It is proven that the description of student learning outcomes in the subjects of the Qur'an and the hadith in the Arrahmah Air Meles Atas MA as objects of research is not good, of course there are factors that influence it. In order to answer these questions, a study was conducted with a qualitative approach by observing learning activities and conducting interviews with teachers as research subjects. It was concluded that there were several factors that caused the low student outcomes, namely low motivation, lack of ability to read and write verses, and hadiths, learning media is not complete and the allocation of time is too minimal contributed to learning outcomes of the subjects of the Koran and hadith are low.Keywords: Learning Outcomes, learning readiness, motivation, learning media